2009
DOI: 10.1002/apj.322
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodenitrogenation of quinoline and its intermediates over sulfided NiW/γ‐Al2O3 in the absence and presence of H2S

Abstract: Hydrodenitrogenation (HDN) reactions of quinoline and its intermediates were carried out at 300-420• C and 2-6 MPa over sulfided NiW/γ -Al 2 O 3 in the absence and presence of H 2 S. The results show that temperature and pressure have a drastic effect on nitrogen removal and production distribution in the HDN of quinoline. 1,2,3,4-tetrahydroquinoline THQ1 mainly underwent dehydrogenation to quinoline and then hydrogenated to 5,6,7,8-tetrahydroquinoline (THQ5), and decahydroquinoline (DHQ) following by ring ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…According to the related research, for the hydrogenation reaction, the temperature should not be too high. 39 In addition, the appropriate pressure and the lower LHSV [40][41][42][43] are benecial to the hydrogenation reaction. In this study, the temperature, pressure and LHSV varied in the range of 340-400 C, 4-10 MPa and 0.4-1.0 h À1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the related research, for the hydrogenation reaction, the temperature should not be too high. 39 In addition, the appropriate pressure and the lower LHSV [40][41][42][43] are benecial to the hydrogenation reaction. In this study, the temperature, pressure and LHSV varied in the range of 340-400 C, 4-10 MPa and 0.4-1.0 h À1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Postulated HDN mechanisms of model compounds such as indoles, pyridines, quinoline and iso-quinoline have been summarized by few authors [2][3][4][5][6][7][8][9][10]. Also, number of studies has been reported on the steric effect of methyl groups on HDS model compounds such as thiophenes, benzothiophene and dibenzothiphene, but only few studies reported on HDN model compounds such as indoles and pyridines [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Quinoline HDN led to two intermediates formation, such as 1,2,3,4-tetra hydro quinoline (1-THQl) and 5,6,7,8-tetra hydro quinoline in which HYD to 1-THQl was faster as compare to 5-THQl though equilibrium attained [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Also, HYD steps assessed first order but dependent on H2 partial pressure, hydrogenolysis represented by lower-order reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex mainly consisting of condensed arenes along with small amounts of heteroatom-containing species. Many efforts have been attempted on the catalytic hydroconversion (CHC) of model compounds due to the complexity of HTCT. The CHC includes the hydrogenation of aromatic rings (ARs) and heteroatom removal. …”
Section: Introductionmentioning
confidence: 99%